2004
DOI: 10.22358/jafs/74081/2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent watering on dry matter intake and body weight of male Ethiopian Somali goats

Abstract: Twenty-six male Ethiopian Somali goats were used. Access to water every 48, 72 or 96 h reduced (P<0.001) the mean water intake (ml/kg W and ml/kg W 0.75 ) and the water to feed ratio (ml/g DMI) compared to every 24 h with no difference between the 48 and 72 h. Dry matter intakes (g/kg W and g/kg W 0.75 ) were reduced only at 96 h (P<0.01). Final body weight and daily gain were not affected by the watering regimes. We conclude that this goat breed tolerate prolonged periods of dehydration and can be watered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In a water restriction experiments that were conducted at an ambient temperature of 22°C, Maloiy et al [70] reported an increasing and significant reduction in feed intake from Turkana goats (−58.30%) to fat-tailed sheep (−48.00%) and Zebu (−50.00%). However, some studies reported that feed intake is not significantly affected by water restriction [20,71], because the ruminants can store up water for use during scarcity or shortfalls. According to Hadjigeorgiou et al [72], dry matter voluntary intake in sheep water-restricted for 1h per day or given 65% of the ad libitum intake of water was not affected.…”
Section: Adaptive Responses Of Small Ruminants To Water Shortages mentioning
confidence: 99%
“…In a water restriction experiments that were conducted at an ambient temperature of 22°C, Maloiy et al [70] reported an increasing and significant reduction in feed intake from Turkana goats (−58.30%) to fat-tailed sheep (−48.00%) and Zebu (−50.00%). However, some studies reported that feed intake is not significantly affected by water restriction [20,71], because the ruminants can store up water for use during scarcity or shortfalls. According to Hadjigeorgiou et al [72], dry matter voluntary intake in sheep water-restricted for 1h per day or given 65% of the ad libitum intake of water was not affected.…”
Section: Adaptive Responses Of Small Ruminants To Water Shortages mentioning
confidence: 99%
“…In a recent experiment, growing Somali male goats were watered at 24, 48, 72, or 96-h intervals. They performed well even when the watering interval lasted 72 h. 10 Under conditions of dehydration, moisture evaporation is reduced to conserve water, 11 a strategy that results in partial abandonment of homeothermy. The experiment by Schmidt-Nielsen et al 12 in camels is a classic example.…”
Section: Fluid Balancementioning
confidence: 99%
“…Water restriction had no effect on feed intake in the study of Mengistu et al (2004) and suggesting that ruminants are able to accumulate water in reserve to be used in periods of reduced water supply. Water deprivation induces a decrease in body fluid content and an increase in its osmolality.…”
Section: Water Restriction and Performancementioning
confidence: 83%